2014
DOI: 10.1080/02791072.2014.921747
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Versus Simultaneous Use of Alcohol and Non-Medical Use of Prescription Drugs: Is Simultaneous Use Worse for Mental, Social, and Health Issues?

Abstract: This study investigated the difference between concurrent and simultaneous use of alcohol and non-medical use of prescription drugs (NMUPD) in relation to mental, social, and health issues. The 544 study participants of the Swiss ongoing Cohort Study on Substance Use Risk Factors (C-SURF) had a combined use of alcohol with NMUPD during the previous 12 months. Alcohol-related problems (i.e., dependence and consequences), as well as mental, social, and health concerns (i.e., depression, general mental/physical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
10
0
1
Order By: Relevance
“…that most polysubstance use is simultaneous (Baggio et al, 2014;McCabe et al, 2006;Quek et al, 2013;Subbaraman & Kerr, 2015). Reliable and valid measures are essential for describing substance use patterns, evaluating effectiveness of interventions, and enacting harm-prevention policies.…”
Section: Discussionmentioning
confidence: 99%
“…that most polysubstance use is simultaneous (Baggio et al, 2014;McCabe et al, 2006;Quek et al, 2013;Subbaraman & Kerr, 2015). Reliable and valid measures are essential for describing substance use patterns, evaluating effectiveness of interventions, and enacting harm-prevention policies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent surveys have ascertained that PSU risk is particularly high among college students (Gledhill-Hoyt et al, 2000;Johnston et al, 2004;Mohler-Kuo et al, 2003;Barrett et al, 2006; National Center on Addiction and Substance Abuse at Columbia University, 2007;O'Grady et al, 2008) with alcohol, tobacco, and cannabis being the three most widely used substances in this population (Lipari and Jean-Francois, 2016). Indeed, these drugs share similar trajectories of use among emerging adults, with high rates of comorbidity (Jackson et al, 2008) and simultaneous consumption (Martin et al, 1992;Baggio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Third, due to data limitations, we cannot distinguish between simultaneous and concurrent polydrug use. Recent research has demonstrated that simultaneous polydrug use is thought to be of greater mental, social, and health consequence compared with concurrent polydrug use (Baggio et al, 2014). Future research should examine possible differences in aggression between concurrent and simultaneous polydrug users versus monodrug users.…”
Section: Discussionmentioning
confidence: 99%